The Role of Visual, Semantic and Sensual Aspects of Architecture in Perpetuating the Memory of the Past – the New Synagogue in Mainz - Sowińska-Heim, Julia (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
Thanks to its expressive form, the New Synagogue and the Jewish Community Centre in Mainz erected in 2008–2010 is a powerful sign in the urban space, creating a sort of aesthetic energy of the place. Its shape and influence results from the special synergy of an ultra-modern form and content deeply rooted in tradition. Serving particular functions, the building at the same time becomes an important urban art piece, determining and defining identity of the place.